ORGANIZATIONAL AND LEGAL MECHANISMS FOR ENSURING THE SAFETY OF ECONOMIC ENTERPRISES - Bezzubov, Dmytro; Denysiuk, Maryana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Goal: to formulate proposals for improving the legal framework for creating a security system for the activities of enterprises/business entities based on the results of an analysis of the organizational, legal and economic components of their activities, identified problems in ensuring security, and outlining models for ensuring the security of the activities of business entities and the security of entrepreneurship in particular. Research methods: the main scientific methods of formal logic, system analysis and the classification method were used. The system analysis method was applied accordingly to determine special and general mechanisms of legal support for the activities of the enterprise. The method of formal logic allowed to determine scientific views on the problems of business security. The classification method allowed us to identify ways to further improve the institutional foundations of the administration of enterprise security. The forecasting method allowed us to outline ways to improve the organizational component of enterprise security. The modeling method allowed us to determine the place and role of organizational and legal elements in the system of ensuring the security of business entities. Results: the study of the legal foundations of administration of ensuring the highest level of enterprise security is part of the study of problems of applied economic science, philosophy of law, economic and international economic law. The main functions, principles and methods of ensuring the security of business entities are determined. The model of enterprise security is proposed as a set of conditions and indicators of its activity that form the environment of safe activity. The category of "autopoiesis of enterprise security" is defined, which is understood as an element of self-regulation of the enterprise security system. The results presented in this scientific article allow us to determine further steps for studying the problems of the organizational and legal component of ensuring the security of the activities of business entities. Discussion: the problems of increasing the level of security of business entities are applied from the perspective of the development of the philosophy of law and economic law. The proposal for the formation of an organizational and legal model of business security is under discussion. In a broad sense, it provides for a system of measures to ensure business security at the state level. Such measures are aimed at countering threats and dangers in all areas of society’s functioning for the sake of stability and guarantees of achieving successful results of economic activity.